Conjugated, trans‐Spanning Ligands as Models for Multivalent p‐Phenyleneethynylenes. Issue 5 (19th January 2016) - Vang, Herh G.; Driscoll, Zakarias L.; Robinson, Emily R.; Green, Casey E.; Bosch, Eric; Bowling, Nathan P.
Abstract: A conjugated, pyridine‐containing, phenylethynyl ligand that forms complexes with Ag I and Pd II has been developed. NMR titration studies with Pd II reveal a stoichiometric binding of the ligand to the metal atom, while similar studies with Ag I reveal a binding that is dynamic on the NMR timescale. Analysis of the NMR spectroscopic data by Job's plot analysis and non‐linear curve fitting of a titration curve reveals a 1:1 binding ratio of ligand/silver cation and an association constant of K a = 53M –1 . X‐ray crystal structures of the ligand–metal complexes suggest ample room for the nearly barrierless rotation of the unsubstituted central benzene ring of the para ‐phenylethynyl chain. Subtle electronic differences in substituted systems provide some evidence of impaired rotation. Abstract : Conjugated ligands: A trans ‐spanning ligand that binds Ag I and Pd II has been developed and studied by X‐ray crystallography and 1 H NMR spectroscopy. UV/Vis spectroscopy was used to investigate what effect metal binding might have on the conjugation in the para ‐phenyleneethynylene backbone.